In Vivo Anti-Vibrio Evaluation of Sponge-Associated Bacteria on the Survival Rate of Litopenaeus vannamei Infected with Pathogenic Vibrio Species - Jepri Agung Priyanto,; Galuh Adhiyaksa Ashari,; Munti Yuhana,; Aris Tri Wahyudi, (Tropical Life Sciences Research, 2023)
Sponge-associated bacteria are considered a rich source of bioactive compounds particularly to reduce the risk of Vibrio harveyi and Vibrio parahaemolyticus infection. The present study aimed to analyse the effectiveness of 19 isolates to control Vibrio infection in vivo. All 19 isolates displayed a non-pathogenic characteristic on shrimps (cell density of 106 cells/mL) as analysed using the pathogenicity test. The mortality caused by both Vibrio spp. on 50% of the shrimp population (LC50 value) had a cell density of 105 cells/mL as determined using the proportion interval method. On the basis of the challenge test, all isolates improved the survival rate of infected shrimps in diverse effectivities up to 89%, which was nearly 30% higher than the infected control. Two isolates coded as D6.9, and P5.20 reduced shrimp mortality after infection with Vibrio spp. 16S rRNA-based identification showed these isolates were closely similar to different genera of Bacillus and Staphylococcus. The extract derived from the most prospective isolate, D6.9, was dominated by 1-hydroxy-6-(3-isopropenyl-cycloprop-1-enyl)-6-methyl-heptan-2-one, hexadecanoic acid, 4-epicyclomusalenone [(24S)-24-methyl-28-norcycloart-25-en-3-one], and 2,4-dimethyl acetoacetanilide. This observation suggested these isolates characterised by in vivo anti-Vibrio activity need to be further developed as biocontrol candidates.